Epidermolytic hyperkeratosis in inflammatory linear verrucous epidermal nevus - Naser Tayyebi Meibodi; Yalda Nahidi; Zari Javidi (Wolters Kluwer Medknow Publications, 2011)
Epidermolytic hyperkeratosis presents with perinuclear vacuolization of the keratinocytes in spinous and granular layers, keratinocytes with ill-defined limits, which leads to a reticulate appearance of the epidermis, an increased number of variously shaped and sized basophilic keratohyalin granules and the same sized eosinophilic trichohyalin granules, at any level of epidermis, mainly in the stratum granulosum, and compact hyperkeratosis. This minor reactive pathologic reaction pattern of skin is found in large variety of diseases. This paper is the first case report of such pattern in inflammatory linear verrucous epidermal nevus. Our case is of a 23-year-old man with pruritic verrucous lesions of trunk and extremities initiated since 13 years ago. Physical examination revealed white linear hyperkeratotic lesions, some of them on erythematous background and also classic epidermal nevus. No skeletal, ophthalmic, and nervous system involvement was detected. Microscopic study of pruritic verrucous lesions showed psoriasiform acanthosis, mild papillomatous, hyperkeratosis, and epidermolytic hyperkeratotic changes in hair follicles and acrosyrinx accompanied with moderate perivascular inflammation.